A novel 2kWe biomass-organic rankine cycle micro cogeneration system - Daminabo, Ferdinand Frank Oko (2009)
Energy is potentially at the hub of modern civilization and right from Industrial Revolution, technology has refined and redefined the way we use energy; but technological advancement in all spheres will continue to depend and use energy to progress. However, fossil fuels (coal, gas, oil) have remained the dominant energy resource accounting for a larger proportion of world energy consumption when compared to nuclear energy and renewable energy resources. There are mounting fears of both the climate and our environment reaching a characteristic tipping point due to global warming. This is associated with the relentless use of fossil fuels and uncontrolled emissions of greenhouse gases. The persistent trend has triggered the need for alternative and renewable energy options which are now being considered and pursued globally to avert the possibility of climate change attaining a state of irreversibility. This research describes the development of a novel 2kWe biomass fired Organic Rankine Cycle (ORC) system intended for remote off-grid locations, employing a multi-vane expander as the prime mover. The expander is a four vane model 6AM-FRV-5A 3kW Gast Air motor manufactured by Gast Manufacturing Inc. The prime mover will harness power produced by high pressure vapour to generate torque and rotational motion on the shaft and the mechanical energy generated is converted to electricity by means of an automotive alternator. The conversion of low and medium temperature heat from biomass to electricity by using low cost, lightweight and low maintenance expander as well organic substances or hydrofluoroether, HFE 7100 and HFE 7000 is the subject ofthis research. In order to assess and predict the performance of the system an EES simulation of a basic cycle is carried out in order to compare the the outcome with the actual cycle. A preliminary air test of the system was also carried out to have a perspective on actual performance using compressed air. However, the organic substance, hydrofluoroether (HFE) to be used in further tests is selected because of its thermodynamic properties of having a lower specific volume and higher molecular weight than steam allowing for smaller, less complex, less costly energy applications like expanders and smaller diameter tubes to be employed for low temperature micro system. This is achieved through a phase change transformation in a Rankine cycle process between specified temperature limits when compared to turbines which operate at higher temperature and pressure. An experimental study and initial testing is carried out using a Chromalox- Model CES-12, 9 kW boiler providing temperatures between 100oC and 115oC and test measurements collated and analysed to predict performance and assess outputs and possibly fluctuations in the system. A test involving the use of the biomass boiler is carried out later and analysed results compared with that of the electric boiler. The process will involve the supply of heat from the biomass boiler and the high pressured vapour generated in the ORC cycle is expanded through the prime mover with a fall in temperature and pressure at the exhaust and exiting as saturated vapour or a mixture of vapour and liquid. The energy stored in the working fluid in the vapour state is converted to electricity by work on the shaft while the exhaust heat can be tapped for domestic uses as thevapour is expanded down to low pressure in the condenser and the saturated liquid is pumped to a high pressure in the evaporator to resume the cycle.